Pengaruh Kepemimpinan, Motivasi, Kemampuan Dan Iklim Kerja Terhadap Kinerja Pegawai Yayasan Pendidikan Mawaridussalam - Yusniar Yusniar (JURNAL AGRICA, 2018)
The aim of this study was to determine the effect of leadership, motivation, ability and work climate on employee performance. This research was conducted at the Education Foundation of Mawaridussalam. The population is all employees of the production department of 40 employees. Overall population used as a sample. The variables in this study consists of a free variable (X) is composed of: leadership (X1), motivation (X2), ability (X3) and Work Climate (X4). The dependent variable (Y) is the employee's performance (Y). The analysis used in this study is multiple regression analysis. The results showed that simultaneous independent variables consisting of leadership, motivation, ability and work climate has a significant effect on the dependent variable employee performance. Evidently the Sig F <of α, and of the value of the correlation coefficient indicates a strong correlation between the dependent and independent variables. Partially independent variables of leadership, motivation, ability and climate significant effect on the dependent variable performance of each employee with the Sig t <α. The independent variables that have a dominant influence on the performance of an employee is working climate. Keywords: leadership, motivation, ability, organizational climate and performance